Recurrence of Febrile Convulsions - Taslim S Soetomenggolo (Indonesian Pediatric Society Publishing House, 2018)
During two years, 92 patients who experienced first febrile convulsion were followed-up in the Pediatric Neurology Clinic, Department of Child Health, Cipto Mangunkusumo Hospital, Jakarta for at least one year. Of the 92 patients 58 (63%) were males and 34 (37%) females. Most of the patients were less than 4 years, and only 6 patients (6,5%) aged more than 4 years. Eight (8, 7%) of the 92 patients suffered from recurrence of febrile convulsions, and in 5 of them the recurrence occurred within the first 6 months of follow-up. The recurrences of febrile convulsions occurred mostly in patients less than one year of age, those with tonic seizures, those with neurological disorders, and those who had history of epilepsy in their family. In this study the occurrence of recurrent febrile convulsions in patients with normal EEG was higher than that in patients with abnormal EEG.